The Impact of Financial Literacy Training for Migrants at Destination - Gibson, John; McKenzie, David; Zia, Bilal (World Bank, Washington, DC, 2013)
Lowering the cost of sending remittances has become a major goal of policy efforts in migration, and an area the World Bank has worked on across the globe. Two main channels for lowering these costs are regulatory reforms to promote competition and the introduction of new products; and efforts to increase the disclosure of costs of remitting money through websites. However, the success of such policies depends on the ability of migrants to understand how to use the different methods available for remitting, and on their understanding of the costs implied by each method. Existing evidence suggests migrants often lack knowledge in these areas, suggesting scope for financial literacy efforts to change their behavior.